2015
DOI: 10.1111/oik.02324
|View full text |Cite
|
Sign up to set email alerts
|

Herbivores limit the population size of big‐leaf mahogany trees in an Amazonian forest

Abstract: The Janzen–Connell hypothesis proposes that specialized herbivores maintain high numbers of tree species in tropical forests by restricting adult recruitment so that host populations remain at low densities. We tested this prediction for the large timber tree species, Swietenia macrophylla, whose seeds and seedlings are preyed upon by small mammals and a host‐specific moth caterpillar Steniscadia poliophaea, respectively. At a primary forest site, experimental seed additions to gaps – canopy‐disturbed areas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…We found significant distance‐dependent effects of herbivory for Triadica in the native range but not in the introduced range where herbivore damage was always extremely low. Herbivorous insects have been found to cause distance‐ or density‐dependent mortality (Cardenas, Valencia, Kraft, Argoti, & Dangles, ; Katz & Ibanez, ; Norghauer et al, ), as several studies show distance‐ and density‐dependent effect by recording boreholes, mines and chewing from herbivores (Cardenas et al, ; Katz & Ibanez, ; Mangan et al, ; Norghauer et al, ; Visser et al, ), and herbivore manipulations demonstrated distance‐dependent impacts of insects (Sullivan, ). In this study, our field common garden and field survey results showed that Triadica leaf damage percent was much higher in the native range than the introduced range.…”
Section: Discussionmentioning
confidence: 99%
“…We found significant distance‐dependent effects of herbivory for Triadica in the native range but not in the introduced range where herbivore damage was always extremely low. Herbivorous insects have been found to cause distance‐ or density‐dependent mortality (Cardenas, Valencia, Kraft, Argoti, & Dangles, ; Katz & Ibanez, ; Norghauer et al, ), as several studies show distance‐ and density‐dependent effect by recording boreholes, mines and chewing from herbivores (Cardenas et al, ; Katz & Ibanez, ; Mangan et al, ; Norghauer et al, ; Visser et al, ), and herbivore manipulations demonstrated distance‐dependent impacts of insects (Sullivan, ). In this study, our field common garden and field survey results showed that Triadica leaf damage percent was much higher in the native range than the introduced range.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, host-specific mutualists can increase the abundance of a particular host species, hence reducing community diversity, in line with the mutualistic effects seen in positive PSF, thereby comprising a "reverse Janzen-Connell effect" (Connell and Lowman 1989;Zahra et al 2021). The Janzen-Connell hypothesis is essentially a PSF process except in cases when aboveground herbivory is the main driver (Norghauer et al 2016).…”
Section: Janzen-connell Hypothesismentioning
confidence: 99%
“…Locally, herbivory often increases where patches of forest are less diverse or where associational resistance is lacking (Barbosa et al 2009, Alvarez‐Loayza and Terborgh 2011, Massad et al 2013, Norghauer et al 2016, Jactel et al 2021). At the sites included in this study, Piper diversity, measured as both species richness and Simpson's index of leaf area, actually led to greater skew and dispersion of generalist herbivory (Fig.…”
Section: Discussionmentioning
confidence: 99%